DERADIKALISASI ANAK-ANAK MANTAN TERORIS MELALUI PENDIDIKAN BERBASIS MULTIKULTURALISME - Arief Hidayat Afendi; Toto Santi Aji (PGSD Universitas Muhammadiyah Cirebon, 2020)
The spread of social conflicts that have occurred is clear evidence, such as the development of terrorist groups in various parts of the world in various forms. Victims of terrorism are not only those who died due to acts of terrorism, but including victims are families and children of terrorism perpetrators who do not know the activities carried out by their husbands or fathers. Coupled with the negative stigma and bullying behavior towards them sometimes leads to what is called